Wallichinine reverses ABCB1-mediated cancer multidrug resistance - Lv, Min (Am J Transl Res, 2016)
Overexpression of ABCB1 in cancer cells is one of the main reasons of cancer multidrug resistance (MDR). Wallichinine is a compound isolated from piper wallichii and works as an antagonist of platelet activiating factor receptor to inhibit the gathering of blood platelet. In this study, we investigate the effect of wallichinine on cancer MDR mediated by ABCB1 transporter. Wallichinine significantly potentiates the effects of two ABCB1 substrates vincristine and doxorubicin on inhibition of growth, arrest of cell cycle and induction of apoptosis in ABCB1 overexpressing cancer cells. Furthermore, wallichinine do not alter the sensitivity of non-ABCB1 substrate cisplatin. Mechanistically, wallichinine blocks the drug-efflux activity of ABCB1 to increase the intracellular accumulation of rhodamine 123 and doxorubicin and stimulates the ATPase of ABCB1 without alteration of the expression of ABCB1. The predicted binding mode shows the hydrophobic interactions of wallichinine within the large drug binding cavity of ABCB1. At all, our study of the interaction of wallichinine with ABCB1 presented herein provides valuable clues for the development of novel MDR reversal reagents from natural products.